Establishing regions of interest of the lower leg and ankle for perioperative volumetric assessment with a portable 3D scanner in orthopedic and trauma surgery – a pilot study - Roman Taday; Erik Schiffner; Sebastian Viktor Gehrmann; Lena Marie Wilms; Robert Alexander Kaufmann; Joachim Windolf; David Latz (Journal of Foot and Ankle Research, 2023)
Abstract Background Soft tissue swelling assessment benefits from a reproducible and easy to use measurement method. Monitoring of the injured lower extremity is of clinical import during staged soft tissue management. Portable 3D scanners offer a novel and precise option to quantify and contrast the shapes and volumes of the injured and contralateral uninjured limbs. This study determined three regions of interest (ROI) within the lower extremity (lower leg, ankle and foot), that can be used to evaluate 3D volumetric assessment for staged soft tissue management in orthopedic and trauma surgery. Methods Twelve healthy volunteers (24 legs) were included in this cohort study. Scans of all three ROI were recorded with a portable 3D scanner (Artec, 3D scanner EVA) and compared between the right and left leg using the software Artec Studio (Arctec Group, Luxemburg). Results Mean volume of the right leg was 1926.64 ± 308.84 ml (mean ± SD). ROI: lower leg: 931.86 ± 236.15 ml; ankle: 201.56 ± 27.88 ml; foot: 793.21 ± 112.28 ml. Mean volume of the left leg was 1937.73 ± 329.51 ml. ROI: lower leg: 933.59 ± 251.12 ml; ankle: 201.53 ± 25.54 ml; foot: 802.62 ± 124.83 ml. There was no significant difference of the overall volume between right and left leg (p > 0.05; overall volume: △ difference: 29.5 ± 7.29 ml, p = 0.8; lower leg: △ difference: 21.5 ± 6.39 ml, p = 0.8; ankle: △ difference: 5.3 ± 2.11 ml, p = 0.4; △ difference: 16.33 ± 4.45 ml, p = 0.8. Conclusion This pilot study defines three regions of interest of the lower leg and demonstrates no difference between the right and left side. Based on these ROI, further studies are needed to evaluate the clinical applicability of the scanner.